-20-19g=-20g

Simple and best practice solution for -20-19g=-20g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20-19g=-20g equation:



-20-19g=-20g
We move all terms to the left:
-20-19g-(-20g)=0
We get rid of parentheses
-19g+20g-20=0
We add all the numbers together, and all the variables
g-20=0
We move all terms containing g to the left, all other terms to the right
g=20

See similar equations:

| 5x=3(x–1)+(3+2x) | | 10−2t=–4t | | 9y+10=-8- | | 9=2f | | 4(-1-x)+3x=-2x-2 | | 2(3x+4)+3=10x9 | | j+3=-4+8j | | x+2/x-3=x/x-4 | | 0.5x2=-2 | | A=54-18x | | 2r+8(-5r-6)=14-7r | | -4=3u-3u-4 | | -12v+17=-19-9v | | 2x2+12x+45=0 | | 9=7+8a-6a | | 106*2y=180 | | 10v=14+8v | | 35-8n=7(8n+5) | | (1)/(3)x-6=0 | | -8+6g=8g+2 | | -10.6u-1.3=-10.4u | | 20+3•x=8•5-2 | | 1/2(5x-8)=2x | | 8x14=2x+50 | | -u-8=4+4u+3 | | 5y​ −3=−6 | | 2x+13+16x-4=153 | | 5-y=y+24 | | -6-(-8)+6=x | | 2x+57+4x-3=180 | | 8-6x+6x-9=20-5x | | -21x-15=27 |

Equations solver categories